2019
DOI: 10.1515/nanoph-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient plasmonic nanofocusing on a metallized fiber tip with internal illumination of the radial vector mode using an acousto-optic coupling approach

Abstract: Tip-based plasmonic nanofocusing, which delivers light into a nanoscale region and achieves localized electromagnetic (EM) field enhancement beyond the diffraction limit, is highly desired for light-matter interaction-based super-resolution imaging. Here, we present the plasmonic nanofocusing at the apex of a silver (Ag)-coated fiber tip with the internal illumination of a radial vector mode (RVM) generated directly in an optical fiber based on an acoustically-induced fiber grating (AIFG). As illustrated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Figure 3b,c exhibit the electric-field intensity distribution of plane β excited by a pair of strictly degenerate vector modes with the polarization direction parallel to x-and y-axis The electric field enhancement can be notably influenced by illumination modes for the reason of the polarization-dependent excitation of localized surface plasmon modes [33][34][35]. Our previous work [36][37][38]49,50] demonstrates that cylindrical vector beams (CVB), including APB and RPB, are helpful to improve the field enhancement for their special polarization distribution on the cross-section of the light beam. Here, APB and RPB are adopted to excite the side-face configuration and end-face configuration, the simulation model of which is shown in Figure 4a,d, respectively.…”
Section: Electric Field Enhancement Based On Lsprmentioning
confidence: 88%
“…Figure 3b,c exhibit the electric-field intensity distribution of plane β excited by a pair of strictly degenerate vector modes with the polarization direction parallel to x-and y-axis The electric field enhancement can be notably influenced by illumination modes for the reason of the polarization-dependent excitation of localized surface plasmon modes [33][34][35]. Our previous work [36][37][38]49,50] demonstrates that cylindrical vector beams (CVB), including APB and RPB, are helpful to improve the field enhancement for their special polarization distribution on the cross-section of the light beam. Here, APB and RPB are adopted to excite the side-face configuration and end-face configuration, the simulation model of which is shown in Figure 4a,d, respectively.…”
Section: Electric Field Enhancement Based On Lsprmentioning
confidence: 88%
“…61,95,133 Furthermore, we have theoretically and experimentally presented the nanofocusing characteristic of several metal-coated fiber tips under RPB excitation in the visible band, providing an effective guideline for designing the background-free tip-enhanced Raman spectroscopy system. [153][154][155] Combining the azimuthal polarization characteristics of APB with the spatial symmetry characteristics of the silver nanoprism arrays, 156 the sensitivity of surface-enhanced Raman spectroscopy has been enhanced by a factor of 3.3 × 10 7 . In addition, in the fields of fiber communications, Ryf et al demonstrated mode-division multiplexing based on six CVBs or VBs that carried a 40 Gb∕s signal over 96 km in few-mode fiber, 157 and it significantly increases the transmission capacity of fiber communication systems.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Several studies demonstrate that the use of plasmonic structures surrounding the fiber could help confine and concentrate light at the nanoscale. [19][20][21][22] Also, structures made of high-index dielectrics 23 or metals 24 have been shown to enable sub-diffraction light confinement. These studies usually assume single-mode optical fibers and therefore do not consider the modedivision demultiplexing of guided light in tapered optical fibers.…”
Section: Introductionmentioning
confidence: 99%